(untitled) - Wilson, Alan R. (Ontario, Canada, 1999)
Before the Flood takes place in a time when satellite malls didn't hide the horizon, when the best hockey players were found on six teams, when towns were as individual as people. Forty miles to the south, construction is about to begin on a massive dam which will alter the region forever.
Keywords: Canadian fiction,Canadian literature; 20th century